2010
DOI: 10.1016/j.neuropharm.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor gating in neurotensin-1 receptor null mice

Abstract: BACKGROUND Converging evidence has implicated endogenous neurotensin (NT) in the pathophysiology of brain processes relevant to schizophrenia. Prepulse inhibition of the startle reflex (PPI) is a measure of sensorimotor gating and considered to be of strong relevance to neuropsychiatric disorders associated with psychosis and cognitive dysfunction. Mice genetically engineered to not express NT display deficits in PPI that model the PPI deficits seen in schizophrenia patients. NT1 receptors have been most stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…We tested our mice at least at post-natal day 90, when the mice had reached adulthood and our results support those of Kinkead and collaborators as we found no significant differences in PPI between genotypes at this age. Our results with NTS1 -/-are consistent with reports by others (Feifel et al, 2010b), who also found no significant differences in baseline PPI between NTS1 -/-mice and their respective WT controls.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We tested our mice at least at post-natal day 90, when the mice had reached adulthood and our results support those of Kinkead and collaborators as we found no significant differences in PPI between genotypes at this age. Our results with NTS1 -/-are consistent with reports by others (Feifel et al, 2010b), who also found no significant differences in baseline PPI between NTS1 -/-mice and their respective WT controls.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous reports on the important role of NTS1 in the modulations of PPI, as found by pharmacological interventions (Caceda et al, 2005;Kinkead et al, 2005). Analysis of startle pulse alone ASR data showed a significant decrease in startle magnitude with amphetamine alone disruption for WT mice, a trend often reported in other studies that have used amphetamine to disrupt PPI (Dulawa and Geyer, 1996;Feifel et al, 2010b;RalphWilliams et al, 2002;Ralph et al, 2001;Ralph et al, 1999;Varty et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations